Lymphocyte/monocyte to lactate dehydrogenase ratio prior to lymphodepletion impact the outcomes of patients with diffused large B cell lymphoma undergoing CAR-T cell therapy - Na Li; Na An; Sha Ma; Jiang Cao; Feng Zhu; Kunming Qi; Zhiling Yan; Hai Cheng; Wei Sang; Wei Chen; Depeng Li; Zhenyu Li; et al. (Cancer Immunology, Immunotherapy)
Abstract Factors associated with outcomes of chimeric antigen receptor (CAR)-T cell therapy in patients with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) have not been fully elucidated. We explored the impact of the prelymphodepletion (pre-LD) lymphocyte to monocyte ratio (LMR) and its ratio to lactate dehydrogenase (LDH) (LMR/LDH) on the efficacy and prognosis of 60 patients with R/R DLBCL undergoing CAR-T cell therapy. The optimal cutoff values for pre-LD LMR and LMR/LDH were 3.583 and 0.0103, respectively. The overall response rate (ORR)s were higher in patients with high pre-LD LMR or LMR/LDH than those with low pre-LD LMR or LMR/LDH (ORR, 100% vs. 65.79%, P = 0.006 and 96.15% vs. 38.24%, P < 0.0001, respectively). Pre-LD LMR/LDH was an independent factor associated with ORR (P = 0.010, odds ratio = 18.757; 95% confidence interval [CI] 2.046–171.975) by multivariate logistic regression analysis. Patients with high pre-LD LMR/LDH had significantly longer progression-free survival (PFS) (median PFS, 29.73 vs. 2.47 months, P < 0.0001) and overall survival (OS) (median OS, not reached vs. 7.4 months, P = 0.0002) than those with low pre-LD LMR/LDH. Multivariate Cox regression analysis showed that pre-LD LMR/LDH and ORR were independent factors affecting PFS (P = 0.030, hazard ratio [HR] = 2.561; 95% CI 1.093–5.999 and P = 0.024, HR = 2.202; 95% CI 1.22–4.369, respectively); pre-LD LMR/LDH was an independent factor affecting OS (P = 0.029, HR = 3.331; 95% CI 1.131–9.807). In conclusion, the pre-LD LMR/LDH was an independent factor associated with ORR and an independent prognostic factor in patients with R/R DLBCL undergoing CAR-T cell therapy.